Assessment of Antidiabetic Potential Using Melia azedarach fruit Extract - Tiwari, Girish Chandra; Prajapati, Manju (Journal of Neonatal Surgery, 2025)
Melia azedarach L, also known as Chinaberry tree, is a well-studied plant native to Southeast Asia. Its leaves, bark, and fruits have been traditionally used for their antiinflammatory, antipyretic, analgesic, and insecticidal properties. The plant contains bioactive compounds like flavonoids, alkaloids, terpenoids, and saponins. Recent studies have shown that extracts from Melia azedarach L have anticancer properties and antimicrobial activity against various pathogens. Ayurveda, a traditional Indian medicinal system, has been practiced for thousands of years. Research on pharmacognosy, chemistry, and clinical therapeutics has been conducted on ayurvedic medicinal plants. Modern medicine, or allopathy, has evolved over time, but its foundation remains rooted in traditional medicine and therapies. Melia azedarach Linn, also known as mahanimba, is a large evergreen tree found throughout India, used for its anthelmintic, antilithic diuretic, emmenagogue, astringent, and stomachic properties. The pharmacognostic evaluation of Melia azedarach includes the identification and characterization of its chemical constituents, which are essential for formulating an effective antidiabetic product. Assessing the antidiabetic potential of Melia azedarach fruit extract involves conducting preclinical and clinical studies to determine its efficacy and safety profile. These studies play a crucial role in establishing the plant's credibility as a natural remedy for managing diabetes. The study aims to assess the acute toxicity and anti-diabetic potential of Melia azedarach fruit extracts. Melia azedarach fruit's methanol extract (MEMA) has been found to have stronger antidiabetic action than its aqueous extract (AEMA). This is likely due to its stimulatory impact on insulin production, improving insulin-dependent gene expression, lipid profile, oxidative stress, and antioxidant defense systems. MEMA also has potent antioxidant capacity due to its high flavonoid content, which reduces damaging radicals. The presence of polyphenols contributes to its effects, including reduced oxidative stress indicators and increased antioxidant protective capacity. The hypotriglyceremic and normolipemic effects of MEMA may be due to glycosides. Thus, Melia azedarach fruit extract could be a potential diabetes treatment agent.